The Psychological State of Farmers in the Agricultural Cultivation of Food Crops during the COVID-19 Pandemic in Java, Indonesia - Rafika Nur Kusumawati; Kharisma Kusuma Wardani; Suntoro Suntoro (Universitas Sebelas Maret, 2021)
This research aims to discover the psychological state of farmers in the agricultural cultivation of food crops during the COVID-19 pandemic. It is a descriptive explorative study which explores the farmers’ opinions regarding their agricultural activities during the COVID-19 pandemic which reached its peak between March and June 2020. During this period, a Large Scale Social Distancing (LSSD) system was enforced in some areas. The data collection was conducted in June 2020 before the implementation of the new normal, involving 634 respondents which spread across 40 districts throughout Java. Throughout the COVID-19 pandemic period, almost all farmers continued to carry out their agricultural activities. Some farmers had implemented the health protocols. According to most farmers’ opinions, doing the agricultural activities made them healthier. With regard to COVID-19, most farmers behave normally, while the rest feel worried. Agricultural extension activities are constrained and hampered by the implementation of physical and social distancing, especially large-scale social restrictions. Seeing the psychological condition of the farmers, where most are continuing to cultivate food crops and only slightly worried about the COVID-19 pandemic, gave hope for the sustainability of agricultural production in the new normal period.